PENERAPAN BIAYA LINGKUNGAN PADA TAMBANG AIR LAYA PT BUKIT ASAM, TBK - Ningsih, Meidiana Mulya; Rianti, Lina; Matofani, Maya; Pratama, Iranda Septa (Media Mahardhika, 2025)
The purpose of this study to analyze the implementation of environmental costs at PT Bukit Asam, Tbk and specifically, its practice at the Cik Ayib mud settling pond mine, Sumatera Selatan. The research method uses a qualitative approach based on secondary data. The study show that environmental costs as the total cost of all estimates required to restore the environment to its original condition is one of the environmental performance indicators related to the general aspects of the GRI standards. The implementation of environmental costs at the mine level is focused on acid mine water management as waste from mining operations. The implementation of environmental costs for the entire mining operations of PTBA is intended for various activities such as reclamation and post-mining activities and PTBA management acknowledges the existence of environmental obligations for reclamation and post-mining as provisions so that it is in accordance with PSAK 57.